How simple is reading in Arabic? A cross‐sectional investigation of reading comprehension from first to sixth grade. (23rd December 2016) - Asadi, Ibrahim A.; Khateb, Asaid; Shany, Michal
Abstract : This study aimed to examine, from a cross‐sectional perspective, the extent to which the simple view of reading (SVR) model can be adapted to the Arabic language. This was carried out by verifying, in both beginning and more skilled readers, whether the unique orthographical and morphological characteristics of Arabic contribute to reading comprehension beyond decoding and listening comprehension abilities. Reading comprehension was evaluated in a large sample of first to sixth‐grade Arabic‐speaking children. The participants' decoding and listening comprehension abilities were investigated together with their orthographic and morphological knowledge. Path analysis indicated that reading comprehension was moderately explained by the SVR (56–38%). Orthographic and morphological knowledge explained an additional 10–22% of the variance beyond that explained by the basic SVR components. These findings demonstrate that certain linguistic aspects of Arabic impact reading processes differently when compared with other languages. The psycholinguistic implications of these findings are discussed in the light of previous findings in the literature. What is already known about this topic? The 'simple view of reading' model explains reading comprehension as the product of decoding and listening comprehension. This model explains between 70% and 83% of the variance in reading comprehension in English, in which the contribution of decoding and listening comprehension varies as a function of the level of the readers. Orthographic transparency and other unique characteristics of the languages studied might influence reading comprehension in these languages What does this paper add? Arabic is a diglossic language that is characterised by relatively unique orthographic and morphological features for which the validity of the simple view of reading (SVR) has not been tested. The basic components of the SVR (decoding and listening comprehension) have explained between 56% and 38% of the variance in reading comprehension in children from the first to the sixth grade. Decoding, as one of the basic components of the SVR, failed to contribute to reading comprehension when orthography and morphology were considered. Implications for practice and/or policy This large‐scale cross‐sectional study is the first of its type to assess reading comprehension in Arabic. The study justifies the necessity to assess the suitability of the SVR in languages with very specific linguistic characteristics such as Arabic. The results emphasise the necessity of considering the complex orthography and the rich morphology of Arabic for improving teaching, assessment and intervention.